2011
DOI: 10.5539/jas.v4n3p175
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Ground-based Remote Sensors for Crop N Management in Sub Saharan Africa

Abstract: Remote sensors have a growing legacy for improving crop N use efficiency (NUE) in several parts of the world. The technology employs crop spectral properties to determine fertilizer rates by matching crop N requirement based on midseason yield potential. Conclusions that the technology is inappropriate for Sub Saharan Africa (SSA) because the farmers use little or no fertilizer, or cannot afford it, are reviewed. Opportunities and applicability using a model concept from the GreenSeeker ® sensor ($4000) are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…African research is starting to adapt PA technology to both large-scale farming (Maine et al, 2007(Maine et al, , 2010 and smaller scale agriculture (Teboh et al, 2012). One of the main uses of GNSS in developing countries is mapping of farm and field boundaries to establish land tenure.…”
Section: Africamentioning
confidence: 99%
“…African research is starting to adapt PA technology to both large-scale farming (Maine et al, 2007(Maine et al, , 2010 and smaller scale agriculture (Teboh et al, 2012). One of the main uses of GNSS in developing countries is mapping of farm and field boundaries to establish land tenure.…”
Section: Africamentioning
confidence: 99%
“…Similar results were communicated by Sultana et al (2014) from a study in Pakistan where NDVI was positively correlated with grain yield at stem elongation (r = 0.888), booting (r = 0.950), and maturity stage (r = 0.927). Although many studies reported a good correlation between Green-Seeker measured NDVI and crop yield, such studies have not been done widely in tropical SSA (Teboh et al 2012). It is obvious from the results of this study that wide testing and evaluation of the GreenSeeker Handheld Optical NDVI sensor is of paramount importance.…”
Section: Correlation Coefficient Between Grain Yield and Ndvi Score A...mentioning
confidence: 86%
“…It can be used to track rainfall, drought conditions and in identifying water resources, thereby alerting farmers beforehand on availability of water and on weather so that capital and crop planning can be done in advance [46]. Normalized Difference Vegetation Index (NVDI) values, which are one of the most important parameters to quantify the crop cultivation process, are used to notify yield prediction and plant growth [47]. Remote sensing instruments on the farm field are used for monitoring abiotic stress agents with the best possible spatial resolution [48].…”
Section: Remote Sensingmentioning
confidence: 99%